Statistical and adaptive signal processing : spectral estimation, signal modeling, adaptive filtering, and array processing - Manolakis, Dimitris G.; Ingle, Vinay K.; Kogon, Stephen M. (Artech House signal processing library., 2005)
This authoritative volume on statistical and adaptive signal processing offers you a unified, comprehensive and practical treatment of spectral estimation, signal modeling, adaptive filtering, and array processing. Packed with over 3,000 equations and more than 300 illustrations, this unique resource provides you with balanced coverage of implementation issues, applications, and theory, making it a smart choice for professional engineers and students alike.